Retrospective Assessment of Risk Factors for Head and Neck Cancer Among World Trade Center General Responders - Bover Manderski, Michelle T.; Black, Kathleen; Udasin, Iris G.; Black, Taylor M.; Steinberg, Michael B.; Giuliano, Anna R.; Luft, Benjamin J.; Harrison, Denise; Crane, Michael A.; Moline, Jacqueline; Passannante, Marian R.; Ohman Strickland, Pamela; et al. (Frontiers in Public Health, 2020)
Objective: To assess the reliability of a questionnaire designed to reconstruct risk factors for head and neck cancer relative to the 9/11 World Trade Center (WTC) response and over the lifetime. Methods: As part of a nested case-control study, 200 WTC Health Program (WTCHP) General Responder Cohort (GRC) members completed a newly-developed study questionnaire via telephone (with a trained interviewer) or online (self-administered). We assessed agreement between measures of tobacco and alcohol use in our questionnaire results and data collected previously during WTCHP-GRC monitoring visits using Cohens Kappa (κ) and intraclass correlation coefficient (ICC) for categorical and continuous measures, respectively. We compared agreement by disease status, survey mode, and year of WTCHP enrollment. Results: We observed high agreement between measures of lifetime, pre-WTC, and post-WTC smoking prevalence (all κ > 0.85) and smoking duration (all ICC > 0.84). There was moderate agreement between measures of smoking frequency (ICC: 0.61–0.73). Agreement between measures of smoking frequency, but not duration, differed by disease status, and agreement between smoking measures was higher for participants who completed our survey by phone than by web. Among cases, there were no differences based on enrollment in the WTCHP before or after diagnosis. Conclusion: Agreement between measures was generally high, although potential reporting bias and a mode effect that should be considered when interpreting analyses of self-reported data in this population; however differential misclassification appears to be minimal. Our questionnaire may be useful for future studies examining similar behavioral risk factors among disaster-exposed populations.